2016
DOI: 10.1089/jwh.2015.5469
|View full text |Cite
|
Sign up to set email alerts
|

Acceptability and Feasibility of Human Papilloma Virus Self-Sampling for Cervical Cancer Screening

Abstract: HPV self-sampling was both acceptable and feasible to participants and clinic staff and may help overcome barriers to screening.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
50
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(60 citation statements)
references
References 43 publications
1
50
2
Order By: Relevance
“…Several well-conducted US studies have implemented HPV self-testing through community health workers and other direct-interaction approaches. 2327,41 Direct one-to-one engagement has many strengths, but requires considerable personnel time and effort. Our approach has the potential to require fewer resources per woman screened.…”
Section: Discussionmentioning
confidence: 99%
“…Several well-conducted US studies have implemented HPV self-testing through community health workers and other direct-interaction approaches. 2327,41 Direct one-to-one engagement has many strengths, but requires considerable personnel time and effort. Our approach has the potential to require fewer resources per woman screened.…”
Section: Discussionmentioning
confidence: 99%
“…Recent evidence suggests that vaginal self‐obtained samples provide sensitivity and specificity equal to clinician‐collected specimens for detecting high‐risk HPV types and cervical intraepithelial neoplasia 2+ . HPV self‐testing acceptability, feasibility and satisfaction studies among Indigenous and ethnic minority women found that HPV self‐testing is preferable to cervical cytology, and potentially eliminates barriers to cervical screening …”
Section: Introductionmentioning
confidence: 99%
“…on subgroup-specific attitudes and beliefs about self-collection (De Alba et al, 2008;Forrest et al, 2004;Howard et al, 2009;Ilangovan et al, 2016;Lofters et al, 2017;Montealegre, Mullen, Jibaja-Weiss, Vargas Mendez, & Scheurer, 2015;Vahabi & Lofters, 2016;Virtanen et al, 2014) all the way through regional and national implementation with subgroup analysis for differences in uptake depending on delivery method (Kobetz et al, 2018;Tranberg et al, 2018). Three studies focused on CCS completion rates in the self-collection group versus standard clinic-based collection (Sewali et al, 2015;Virtanen et al, 2015;Virtanen, Anttila, Luostarinen, & Nieminen, 2011).…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…The most frequently noted time frame was 10 years, more or less, living in the country of resettlement (Barbee et al, 2010;Lofters et al, 2017;Montealegre et al, 2015;Sewali et al, 2015). Only Ilangovan et al (2016) reported on the citizenship status of their study participants. The authors from only two of the 15 articles provided analysis of the relationship between length of time a participant had lived in the country of resettlement, or citizenship status, with specific outcome measures (Barbee et al, 2010;Sewali et al, 2015).…”
Section: Length Of Residence In Country Of Resettlementmentioning
confidence: 99%
See 1 more Smart Citation